2013
DOI: 10.1063/1.4807129
|View full text |Cite
|
Sign up to set email alerts
|

Controlling magnetism of multiferroic (Bi0.9La0.1)2FeCrO6 thin films by epitaxial and crystallographic orientation strain

Abstract: Effects of the tensile and compressive epitaxial strain and the crystallographic orientations on the structural and magnetic properties of (Bi0.9La0.1)2FeCrO6 (BLFCO) films were studied. The BLFCO (001) films (30 nm and 70 nm) were deposited on various single crystal substrates having lattice mismatch with the film in the range of −4.16% to +7.2%. We find that a pronounced ferromagnetic order manifests in the coherently strained films compared to that in the partially strained films. The saturation magnetic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
18
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 23 publications
5
18
1
Order By: Relevance
“…These values are comparable with those obtained by magnetometric measurements in BFCO thin films with weak ferromagnetic behavior. 20,26,29 Similar measurements as in Figure 2 were repeated with the magnetic field oriented perpendicularly with respect to the sample surface, as shown in the supplementary material. 32 Also in this latter case, the magnetization of both Cr and Fe is oriented parallel to the field.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…These values are comparable with those obtained by magnetometric measurements in BFCO thin films with weak ferromagnetic behavior. 20,26,29 Similar measurements as in Figure 2 were repeated with the magnetic field oriented perpendicularly with respect to the sample surface, as shown in the supplementary material. 32 Also in this latter case, the magnetization of both Cr and Fe is oriented parallel to the field.…”
mentioning
confidence: 91%
“…Rocking curves (ω-scan) were used to determine the epitaxial quality, whereas in-plane Φ scans were performed to check the epitaxial relationship between the substrate and thin films. 29 XAS and XMCD measurements were performed on the EPFL/PSI X-Treme beamline at the Swiss Light Source, Paul Scherrer Institut, Villigen, Switzerland 30 and at Advanced Photoelectric Effect (APE) beamline of IOM-CNR at the Elettra synchrotron radiation facility. 31 At the X-Treme beamline, the samples were measured at 2 K temperature with an applied magnetic field of ±6.8 T oriented along the x-ray beam direction; the direction of the magnetic field with respect to the sample was varied by rotating the sample with respect to the circularly polarized x-ray beam.…”
mentioning
confidence: 99%
“…Magnetization should accompany FE DWs in multiferroics (manganites, orthoferrites) as was reported in [26][27][28][29][30][31][32]. The first theoretical predictions of DW magnetoelectric coupling appeared earlier than experiments and were based on symmetry analysis and phenomenological approaches.…”
mentioning
confidence: 93%
“…Highly ordered BFCO films were first reported in a superlattice form prepared by alternating deposition of BiFeO 3 and BiCrO 3 layers . Later, partially ordered BFCO was also reported by several research groups using pulsed‐laser deposition from a single BiFe 0.5 Cr 0.5 O 3 target . The degree of B ‐site ordering was monitored by the intensity ratio ( R ) between the 1-0.166667emtrue/21-0.166667emtrue/21-0.166667emtrue/2‐superlattice and 111‐diffraction conditions, which typically ranges from 0%‐5.1%.…”
Section: Introductionmentioning
confidence: 99%
“…16 Later, partially ordered BFCO was also reported by several research groups using pulsedlaser deposition from a single BiFe 0.5 Cr 0.5 O 3 target. 17,18 The degree of B-site ordering was monitored by the intensity ratio (R) between the 1 ∕ 2 1 ∕ 2 1 ∕ 2 -superlattice and 111-diffraction conditions, 19 which typically ranges from 0%-5.1%. It was reported that the bandgap of the BFCO films is strongly correlated with the B-site cation ordering, and E g varies between 1.4 and 2.6 eV as the R value decreases.…”
Section: Introductionmentioning
confidence: 99%